A corpus-based analysis on the use of MAKE in sinologist Cyril Birch’s English version of Mistress and Maid (Jiaohongji) - Chunli Yu; Yurong Wu (PLoS ONE, 2026)
While corpus-based translation studies have extensively analyzed lexical patterns, they exhibit critical theoretical limitations in integrating translation theories with empirical analysis, particularly in dramatic translation contexts where cultural mediation and audience reception intersect. Existing high-frequency verb research lacks systematic analysis of how individual lexical choices serve multiple simultaneous function—linguistic, cultural, and theatrical—in cross-cultural dramatic translation. This study addresses these gaps through integrated corpus-translation theory analysis of MAKE deployment in Cyril Birch’s English translation of Mistress and Maid (Jiaohongji) , a classical Chinese chuanqi play. Using AntConc 4.1.1 for corpus analysis (158 MAKE instances from 86,047-word corpus) combined with systematic cultural context examination, the research investigates how high-frequency verbs function as cultural bridging mechanisms. Methodological limitations include single-translator focus and potential genre-specific constraints. Analysis reveals five systematic functional categories: delexical verb constructions facilitating cultural concept transfer, causative verb patterns in bridging metaphorical traditions, notional verb usage in supporting plot development, linking constructions creating thematic resonance, and phrasal verb constructions in emotional expression. These patterns demonstrate that high-frequency verb deployment serves strategic cultural mediation functions beyond simple linguistic substitution. Theoretical Contributions: the study validates and refines the application translation universals in dramatic contexts, demonstrating how simplification and explicitation operate through systematic high-frequency verb deployment. It integrates descriptive translation studies with cultural mediation theory, revealing how micro-level lexical choices serve macro-level intercultural communication goals while challenging corpus linguistics’ purely quantitative approaches to translation analysis. Findings offer evidence-based guidance for dramatic translators regarding strategic use of high-frequency verbs to balance source-text fidelity with target-audience accessibility, particularly in contexts requiring cultural sensitivity and dramatic authenticity.